2020
DOI: 10.1504/ijbem.2020.106203
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing continued use intentions in mobile shopping: the case of South Korea

Abstract: With the rapid diffusion of smartphone use, mobile shopping (m-shopping) has become one of the most common ways to buy and sell products and services through the wireless internet based on mobile devices. Given the importance of long-term use intentions, this paper provides an empirical analysis of factors influencing continued use intentions toward m-shopping. Six m-shopping characteristics were derived from a literature review from three perspectives, and a research model was developed based on the expectati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
(130 reference statements)
0
1
0
Order By: Relevance
“…A separate investigation on mobile commerce carried out in Malaysia by (Luqman et al, 2019) shown that the impact of perceived usefulness on both satisfaction and continuance intention was identified as one of the most robust correlations among all major connections. Furthermore, the correlation between perceived usefulness and both satisfaction and continuance intention has been confirmed in various studies conducted in different countries, including South Africa (Maduku & Thusi, 2023), Vietnam (Nguyen & Ha, 2021), Turkey (Bölen & Özen, 2020) South Korea (Kim et al, 2020) and Taiwan (Chen & Demirci, 2019). These studies have demonstrated that perceived usefulness has a substantial impact on both satisfaction and continuance intention.…”
Section: Hypotheses Developmentmentioning
confidence: 59%
“…A separate investigation on mobile commerce carried out in Malaysia by (Luqman et al, 2019) shown that the impact of perceived usefulness on both satisfaction and continuance intention was identified as one of the most robust correlations among all major connections. Furthermore, the correlation between perceived usefulness and both satisfaction and continuance intention has been confirmed in various studies conducted in different countries, including South Africa (Maduku & Thusi, 2023), Vietnam (Nguyen & Ha, 2021), Turkey (Bölen & Özen, 2020) South Korea (Kim et al, 2020) and Taiwan (Chen & Demirci, 2019). These studies have demonstrated that perceived usefulness has a substantial impact on both satisfaction and continuance intention.…”
Section: Hypotheses Developmentmentioning
confidence: 59%